2016
DOI: 10.5551/jat.30775
|View full text |Cite
|
Sign up to set email alerts
|

Altered Plasma MicroRNAs as Novel Biomarkers for Arteriosclerosis Obliterans

Abstract: Aim: Arteriosclerosis obliterans (ASO) of the lower extremities is a major cause of adult limb loss worldwide. A timely diagnosis in the early stages of the disease determines the clinical outcomes, however lacking of palpable symptoms remains the biggest obstacle. This study aimed to screen a cluster of microRNAs (miRNAs) that can be used as biomarker for the ASO in the earlier stages. Methods: Plasma from 3 patients with ASO and 3 healthy controls were profiled to screen altered miRNAs by microarray, then Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 41 publications
1
40
0
Order By: Relevance
“…It has been proposed that hsa-miR-4306, hsa-miR-320e and hsa-miR-320d in plasma may serve as novel biomarkers for the early detection of acute stroke in humans [29]. miR-4306 were was shown to be significantly downregulated both in Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry plasma and in sclerotic samples of patients with arteriosclerosis obliterans compared with controls [30]. Our study indicates that hsa-miR-4306 in plasma was upregulated, whereas hsa-miR-320a was decreased 30 minutes following administration of dexmedetomidine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that hsa-miR-4306, hsa-miR-320e and hsa-miR-320d in plasma may serve as novel biomarkers for the early detection of acute stroke in humans [29]. miR-4306 were was shown to be significantly downregulated both in Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry plasma and in sclerotic samples of patients with arteriosclerosis obliterans compared with controls [30]. Our study indicates that hsa-miR-4306 in plasma was upregulated, whereas hsa-miR-320a was decreased 30 minutes following administration of dexmedetomidine.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the fold-change and P-values thresholds were 1.2 and <0.1, respectively, which are different from those commonly accepted and were used here because of the relatively short time of exposure to dexmedetomidine. Secondly, some miRNAs are expressed in a time-and stage-specific manner [30]. Thus, the expression pattern of dysregulated miRNAs is not always constant and may fluctuate with time.…”
Section: Discussionmentioning
confidence: 99%
“…Cells with a myofibroblastic nature in the LF may be involved in the hypertrophy 22) , thus suggesting that miR-497-5p possibly plays a role in hypertrophy via the promotion of myofibroblast in LF. It has been reported that miR-4306 was significantly decreased in the sclerotic samples of patients with arteriosclerosis obliterans, characterized by fibrosis of the tunica intima 23) . Thus, these miRNAs may also play a role in the fibrotic change of LF.…”
Section: A B Cmentioning
confidence: 99%
“…Total RNA from plasma and tissues was extracted as previously reported [8]. Input RNA (500 ng) was reverse transcribed to cDNA using a miScript II RT Kit (QIAGEN, Duesseldorf, Germany) according to the manufacturer's instructions.…”
Section: Rna Extraction and Real-time Pcrmentioning
confidence: 99%
“…However, it remains a challenge to define the major regulators in these processes. We have previously demonstrated a novel potential biomarker, miR-4463, which showed remarkably elevated expression in the plasma of patients with T2DM and patients with T2DM combined with arteriosclerosis obliterans of low extremity arteries (ASO) [8], suggesting that miR-4463 may be involved in the pathogenesis of T2DM and vascular disease. We further discovered that miR-4463 was induced by H 2 O 2 in a concentration-dependent manner, and miR-4463 promotes H 2 O 2 -induced human umbilical vein EC (HUVEC) apoptosis by enhancing oxidative stress and cellular ROS [9].…”
Section: Introductionmentioning
confidence: 99%